“Tutte le arti in una sola manifestazione”. Il ’Festival de l’Art d’Avant-Garde’ a Marsiglia - Setti, Stefano (Opus Incertum, 2024)
When Le Corbusier’s Unité d’Habitation in Marseille was inaugurated in 1952, it immediately became an icon of the European postwar landscape, used as a place with a multifaceted character from its very beginning. In summer 1956, its interior hosted the first Festival de l’Art d’Avant-Garde, an event encompassing a wide array of artistic expressions including painting, sculpture, dance, and cinema. The lack of spaces specifically designed for the display of modern art contributed to the selection of this venue. Indeed, the festival’s promoters regarded at Le Corbusier’s building as the ideal setting to evoke the zeitgeist through the simultaneous presentation of diverse contemporary languages, aligning with the designer’s lifelong pursuit of the synthesis of the arts. After providing an overview of the event, this paper aims to investigate the role of architecture not only as a device to display the arts, but also as an active protagonist and an “exhibited” object within the show. This latter aspect stands as a unicum in the art-historical panorama of the period, offering an opportunity to reflect on the potential of exhibiting architecture through the interplay of other art forms.